2022
DOI: 10.7759/cureus.32630
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dumping Syndrome and Its Determinants Among Post-Bariatric Surgery Adult Patients at King Fahad General Hospital, Jeddah, 2019–2020

Abstract: BackgroundBariatric surgery is one of the most effective interventions for morbid obesity. Despite its benefits, unwanted consequences such as dumping syndrome (DS) have been reported following the procedure. This study aims to estimate the prevalence of DS and identify the factors associated with it in Saudi Arabia. MethodologyThis cross-sectional study collected data from patients who underwent bariatric surgery at King Fahad General Hospital, Jeddah, Saudi Arabia, in 2019-2020. A validated questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…While female gender, bypass surgery, and anxiety/depression were associated with dumping syndrome, this was not the case for physical HRQoL. The connection between dumping syndrome and female gender [17, 19, 23] is difficult to explain and needs further investigation. The high proportion of women in the present sample (76%) may have contributed to the result, indicating a selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While female gender, bypass surgery, and anxiety/depression were associated with dumping syndrome, this was not the case for physical HRQoL. The connection between dumping syndrome and female gender [17, 19, 23] is difficult to explain and needs further investigation. The high proportion of women in the present sample (76%) may have contributed to the result, indicating a selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence rates for dumping syndrome after obesity surgery vary between 20 and 40% [12][13][14][17][18][19]. With few exceptions [20], bypass surgery is associated with a higher risk for postoperative dumping than other types of surgery such as, e.g., sleeve gastrectomy or gastric banding [12,15,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prevalence study in Saudi Arabia investigated 240 cases who underwent bariatric surgery and found that 31.4% of the patients met the criteria for dumping syndrome. The study identified gender, educational level, and eating habits as predictors of the syndrome [ 101 ].…”
Section: Reviewmentioning
confidence: 99%
“…When RYGB and sleeve gastrectomy are combined, 31% of patients report experiencing dumping symptoms. 23 For sleeve gastrectomy, the highest reported estimate of early dumping symptoms is 41%, 25 whereas it is 26% after RYGB. 18 The presence of late dumping symptoms was reported less frequently: in 11% of patients after RYGB and in 6.7% of patients after sleeve gastrectomy.…”
Section: Epidemiology Of Dumping Syndromementioning
confidence: 99%